Pengaruh Jenis Biochar terhadap Pertumbuhan dan Hasil Beberapa Jenis Cover Crop dalam Tumpang Sari dengan Jagung Varietas Lokal (Zea Mays L) - Antonius Th. Metboki (Fakultas Pertanian, Universitas Timor, 2019)
This study aimed to learn various types of biochar that affect on the growth and yield of cover crops plants in intercropping with local maize varieties, and to study the effect of cover crops plants on soil moisture content and bulk density. This research was conducted on January to July 2018 at the faculty of agriculture demo-plot, Universitas Timor. The intercroping study design used a Strip Plot Design. The first factor is the type of cover crops (C) consisting of 3 levels, i.e lima bean (Phaseolus lunatus) (C1), velvet bean (Mucuna pruriens) (C2), and red mung bean (Vigna anggularis L.) (C3). The second factor is the type of biochar (B) which consists of 4 (four) levels namely without biochar (B0), sawdust biochar (B1), rice husk biochar (B2), siam weed biochar (B3). The results showed that there was no interaction between the legume cover crops with the type of biochar. M. pruriens cover crops has highest soil coverage, lowest soil temperature, and able to maintain soil moisture better than other cover crops. V. angularis cover crops has highest yield productivity while the M. pruriens has not yet produced but had a great soil coverage and highest thicknes which is very well to used as soil cover crops.